#TITLE_ALTERNATIVE# - RAPIK AHMADI (NIM : 95113001), ANDRI
The equity in the land and property tax is necessary to find the equivalent of fact in determining the amount of property tax exemption. The principle of equity that determined by the ability to pay, is measured with three parameters: income, consumption and wealth. To meet the principles of equity, in this study developed parameters tested approaches that could be taken into consideration in calculating property tax exemption that approach the poverty line set by the Central Statistics Bureau of Indonesia (CSBI), World Health Organization and Europe; Indonesian Standard in Simple Healthy Homes, International and thresholds; Minimum Wage Regional; Rate of Inflation and Indonesian Bank Discount Rate, So with this manner, determining equitable property tax exemption can be used as a reference at the location of research in the Village of Campaka in the District of Bandung. The first step in determining of the property tax exemption is to create value change intervals of every IDR 10 million until IDR 200 million. Counting this interval exemption is to look at the potential loss revenues from any changes in value of the interval and data distribution of property tax payable on each taxpayer. The data that required to calculate each parameter approach is the class value of land and building, the exchange rate of dollar against the rupiah, inflation and the value of BI Rate. In determining the value of the land and building classes is adapted from the determination of European poverty line is the median of each class of the earth and the building multiplied by 60%. The results showed that the exemption by using the CSBI poverty line approach is closer to the principle of equity in Indonesia. The poverty line is calculated from minimum spacious dwellings occupied, income and savings from each house hold that no taxed being charged. Moreover, the result of the calculation through the CSBI poverty line did not show any significant differences with the equitable property tax exemption which has been established by the Government of Bandung today.